Fate descriptors for engineered nanoparticles: the good, the bad, and the ugly. Issue 1 (17th October 2014) - Cornelis, Geert
Abstract : Analyzing three existing fate descriptors for engineered nanoparticles highlights the need for a new mindset to calculate available concentrations. Abstract : Developments in hazard identification of engineered nanoparticles (ENP) have not been met with proper fate descriptors to calculate travel distances and the bioavailable concentration of ENP. Three possible fate descriptors for ENP in soils are compared – batch partitioning coefficients ( K d values), batch retention coefficients ( K r values) and column attachment efficiency – in view of both technical and practical aspects of environmental risk assessments of ENP. K d values are deemed not appropriate fate descriptors for ENP because the equilibrium assumption is not valid. The kinetic interpretation of batch studies offered by K r values bears a link to relevant ENP processes in the environment, but interpretation may be confounded by the conditions of high shear during batch tests complicating direct use in transport or bioavailability calculations. Column experiments are, to some extent, also operationally defined and require a more experimentally dedicated approach that does not necessarily lead to a widely carrying physical parameter. Future efforts should therefore be investigated in development of tests that strike a better balance between operational simplicity and technical accuracy.